Economic and power efficiency of application of different systems of fertilizers under winter wheat on typical black soil in Left-bank Forest –steppe of Ukraine - Глущенко, Л. Д.; Калініченко, С. М.; Дорощенко, Ю. І.; Білан, В. М.; Запорожець, Л. М.; Біланович, О. Л. (Scientific Progress & Innovations, 2012)
Application of fertilizers is one of the most important directions of productivity increase of crops and improvement of soil fertility. With the increase of doses of mineral fertilizers the prime cost of 1 cwt of winter wheat grain rose, but a net profit and the coefficient of power efficiency diminished. Exploitation of soil without application of modern technologies of crop growing and, in particular, without taking measures on reproduction of his fertility will result in the catastrophic decline of soil fertility.